A Zöld Szahara: Álom vagy közeli valóság - Steier, József (Afrika Tanulmányok / Hungarian Journal of African Studies, 2008)
Water deficiency in Africa causes serious consequences in nature and society. This article is about those technical developments which might present possible answers to these challenges. Initially the artificial diversion of oceanic air, creating a humid climate or to make the desert plentiful all seemed to be sensational, futuristic and sometimes unrealizable. But after all we have to take all impossible concepts into account to decrease food scarcity and desertification, and to fight the deepening social crisis all over the continent. The most important message from the author is that maybe the only way to turn around the unthinkable degree of crisis is a seemingly unrealistic intervention.